Can Crop Purchase Programs Reduce Poverty and Improve Welfare in Rural Communities? Evidence from the Food Reserve Agency in Zambia - Winnie Fung; Saweda Liverpool-Tasie; Nicole Mason; Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2015)
The last decade has seen a resurgence of parastatal crop marketing institutions in sub-Saharan Africa, many of which cite improving food security and incomes as key goals. However, there is limited empirical evidence on the welfare effects of these programs. This article considers one such program, the Zambian Food Reserve Agency (FRA), which purchases maize from smallholder farmers at a pan-territorial price that typically exceeds maize market prices in surplus production areas. Using both fixed effects and an instrumental variables approach combined with correlated random effects, we estimate the effects of the FRA's maize marketing activities on smallholder farm household welfare. Results suggest that FRA activities have positive direct welfare effects on the small minority of smallholder households that are able to sell to it. However, the results also suggest negative indirect FRA effects, as higher levels of FRA activity in a district are associated with higher levels of poverty.
Keywords: Q12; Q13; Q18; I38; D31; O13; 330; crop marketing boards; strategic grain reserves; maize; smallholder farmers; income; poverty; Zambia; sub-Saharan Africa